An analysis of oral and maxillofacial pathology found in children over a 30-year period - A. V. JONES & C. D. FRANKLIN (IAPD and Blackwell, 2006)
The Department of Oral Pathology in the School of Clinical Dentistry, Sheffield, UK, has recorded all acceded specimens on a computerized diagnostic index database for some time. Because the date of birth and demographic information are recorded, it is possible to retrieve data on patients in a specific age range.